Modeling the effect of defects on the performance of an n-CdO/p-Si solar cell - Chala, S.; Sengouga, N.; Yakuphanoğlu, Fahrettin (Pergamon-Elsevier Science Ltd, 2015)
The interest in the study of Cadmium oxide (CdO) for photonic applications has increased significantly because of its promising electrical and optical properties. Real solar cells based on an n-CdO/p-Si heterostructures show poor photovoltaic performance, however. In this work numerical simulation is used to elucidate this poor performance by considering two cases. CdO is firstly considered as a perfect crystalline semiconductor. The second case models CdO as a semiconductor with continuous distribution of defects states in its band-gap, similar to an amorphous semiconductor, made of two tail bands (a donor-like and an acceptor-like) and two Gaussian distribution deep level bands (an acceptor-like and a donor-like). Evidently the first case produced results far from reality. In the second case, however, and by adjusting the constituents of the band-gap states the open circuit voltage (V-OC) and the short circuit current (J(Sc)) were almost perfectly reproduced but not the fill factor (FF) and the conversion efficiency (eta). The p-type doping of Silicon adjustment has lead to a better reproduction of the two latter parameters. (C) 2015 Elsevier Ltd. All rights reserved.
Conference and Exhibition on Science and Applications of Thin Films (SATF) -- SEP 15-19, 2014 -- Cesme, TURKEY
Keywords: CdO/Si solar cell; Characterisation; Simulation; Defects